(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Technological advancement in ongoing decades has empowered individuals to learn in various ways. Colleges presently have progressively education models to browse, i.e., b-learning and e-learning. In spite of the expanding open doors for understudies and teachers, internet learning additionally brings difficulties because of the nonappearance of direct human contact. Online conditions permit the age of a lot of data identified with learningshowing forms, which offers the likelihood of extricating significant data that might be utilized to improve understudies’ presentation. In this paper, we expect to survey the similitudes and contrasts between Educational Data Mining and Learning Analytics, two moderately new and progressively mainstream fields of research worried about the accumulation, examination, and understanding of education data. Their starting points, goals, contrasts, similitudes, time development, and difficulties are tended to, just like their association with Big Data and MOOCs.